Meeting Once More : The Korean Side of Transnational Adoption - Prebin, Elise (Book collections on Project MUSE., 2012)
A great mobilization began in South Korea in the 1990s: adult transnational adoptees began to return to their birth country and meet for the first time with their birth parents - sometimes in televised encounters that garnered high ratings. What makes the case of South Korea remarkable is the sheer scale of the activity that has taken place around the adult adoptees' return, and by extension, the national significance that has been accorded to these family meetings. This volume offers a contribution to the study of kinship models, migration, and the anthropology of media, as well as to the study of South Korean culture.